Patient Compliance with Postoperative Lower-Extremity Non-Weight-Bearing Restrictions. (21st September 2016) - Chiodo, Christopher P.; Macaulay, Alec A.; Palms, David A.; Smith, Jeremy T.; Bluman, Eric M.
Abstract : Background: A period of non-weight-bearing is prescribed following many orthopaedic injuries and procedures. It is believed that a period of non-weight-bearing is important for proper healing and recovery. The degree to which patients are compliant with non-weight-bearing instructions is unknown. The purpose of this study was to measure patient compliance with a period of prescribed non-weight-bearing. Methods: In this single-blinded study, pressure-sensitive film was embedded into short leg casts of 51 consecutive adult orthopaedic patients with unilateral lower-extremity abnormality who had been instructed to be strictly non-weight-bearing. Sensors were retrieved at the time of cast removal (mean, 24.3 days [range, 7 to 48 days]) and then were analyzed for force distribution and magnitude. Noncompliance was defined as maximum detectable pressure exerted on ≥50% of the film. Patient characteristics and the time of year that the casts were worn were also examined to determine if they correlated with weight-bearing. Results: Fourteen (27.5%) of 51 patients were noncompliant with the non-weight-bearing restriction. Six (42.9%) of the 14 noncompliant patients compared with 11 (29.7%) of the 37 compliant patients experienced an adverse event (p = 0.51). Sex, age, language spoken, body mass index, time in the cast, and the treating surgeon did not have a significant influence on weight-bearing performance (p > 0.05). Significantly greater weight-bearing was found (p = 0.04) in warmer months (June to October) than in colder months (November to March) in the United States. Conclusions: The noncompliance rate with the postoperative non-weight-bearing restriction was 27.5% (95% confidence interval, 15.2% to 39.8%) in this patient group, despite explicit instructions and education about possible complications associated with weight-bearing. The only factor found to have a significant effect on weight-bearing compliance was the time of year that the cast was worn. No significant difference was found between the complication rate of the compliant patients and that of the noncompliant patients. Level of Evidence: PrognosticLevel IV . See Instructions for Authors for a complete description of levels of evidence.